Prolonged Postpartum Persistent Urinary Retention After Cesarean Section: A Case Report and Literature Review - Erin, Recep; Burkankulu Agirbas, Derya; Erin, Kubra Baki; Kulaksız, Deniz (Gynecology Obstetrics & Reproductive Medicine, 2019)
We aimed to present a case of urinary retention that develops after caesarean delivery and persists for 33 days. A 35-year-old G4P2 41-week-old pregnant woman applied to our clinic because she could not urinate on the 4th day after cesarean section. After the examination, it was determined that urine retention developed in the patient. Neostigmine and meropenem treatment was applied. With intermittent catheterization, spontaneous urination started to take place on postpartum day 33. Postpartum urinary retention, which causes maternal morbidity, is a common condition in obstetric care. Therapy is followed by bladder catheterization, antibiotic therapy and periodic catheter withdrawal, and spontaneous massing of the patient is followed and residual urine is checked by ultrasonography after the mass.